2017
DOI: 10.1088/2051-672x/aa7eaf
|View full text |Cite
|
Sign up to set email alerts
|

Effect of graphite on folded metal occurrence in honed surfaces of grey and compacted cast irons

Abstract: Grey cast iron (GCI) and compacted graphite iron (CGI) are the most employed materials to manufacture cylinder liners. The use of diamond tools to hone the surfaces resulted in an increase of the so-called folded metal occurrence. This irregularity can reduce the performance of engines and investigations to understand it have been made. In this sense, the current study aims to correlate the variation of graphite and the folded metal occurrence. Different samples of GCI and CGI were extracted directly of engine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…It was reported that in the direction of scratching, passage of indenter causes cracks to be formed in the center of the graphite within the lamellas means that the graphite being compressed and then extruded from its pocket. In addition, do Vale et al 31 investigated the effect of graphite on folded metal occurrence in honed surface of grey and compacted cast iron. Based on their work, because of the low strength of graphite compared to metallic matrix and due to the pressure imposed by the honing process, graphite is extruded.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that in the direction of scratching, passage of indenter causes cracks to be formed in the center of the graphite within the lamellas means that the graphite being compressed and then extruded from its pocket. In addition, do Vale et al 31 investigated the effect of graphite on folded metal occurrence in honed surface of grey and compacted cast iron. Based on their work, because of the low strength of graphite compared to metallic matrix and due to the pressure imposed by the honing process, graphite is extruded.…”
Section: Resultsmentioning
confidence: 99%
“…In the following years, GrMaTS/UTFPR increased its facilities, acquiring a universal tribometer, an optical interferometer, and other equipment for material characterization. Counting again with the support of the foundry company, a surface feature resulting from the honing of cast irons-folded metal -was well described and deserves to be highlighted [308]. Results of lubricated wear [309] and the combination of plasma and laser technologies to improve the performance of vermicular cast irons [310,311] have been published.…”
Section: Brazilian Tribology: Status Quomentioning
confidence: 97%
“…during the wear study of the cylinder liner, Yang et al had to cut the lining [2]. Often also simple characterisation needs cutting the engine cylinder [3,4]. However, if silicone replica is prepared from those parts of the cylinder surface that are interesting from the point of view of wear (e.g.…”
Section: Introductionmentioning
confidence: 99%